PROMs and PREMs in routine perinatal care: mixed methods evaluation of their implementation into integrated obstetric care networks - Anne L. Depla; Bettine Pluut; Marije Lamain-de Ruiter; Anna W. Kersten; Inge M. Evers; Arie Franx; Mireille N. Bekker (SpringerOpen, 2023)
Abstract Background In the transition towards value-based healthcare, patient-reported outcome and experience measures (PROM and PREM) are recommended by international collaborations and government programs to guide clinical practice and quality improvement. For many conditions, using PROM/PREM over the complete continuum of care requires implementation across care organizations and disciplines. Along PROM/PREM implementation in obstetric care networks (OCN), we aimed to evaluate implementation outcomes and the processes influencing these outcomes in the complex context of care networks across the continuum of perinatal care. Methods Three OCN in the Netherlands implemented PROM/PREM in routine practice, using an internationally developed outcomes set with care professionals and patient advocates. Their aim was to use PROM/PREM results individually to guide patient-specific care decisions and at group-level to improve quality of care. The implementation process was designed following the principles of action research: iteratively planning implementation, action, data generation and reflection to refine subsequent actions, involving both researchers and care professionals. During the one-year implementation period in each OCN, implementation outcomes and processes were evaluated in this mixed-methods study. Data generation (including observation, surveys and focus groups) and analysis were guided by two theoretical implementation frameworks: the Normalization Process Theory and Proctor's taxonomy for implementation outcomes. Qualitative findings were supplemented with survey data to solidify findings in a broader group of care professionals. Results Care professionals in OCN found the use of PROM/PREM acceptable and appropriate, recognized their benefits and felt facilitated in their patient-centered goals and vision. However, feasibility for daily practice was low, mainly due to IT issues and time constraints. Hence PROM/PREM implementation did not sustain, but strategies for future PROM/PREM implementation were formulated in all OCN. Processes contributing positively to implementation outcomes were internalization (understand the value) and initiation (driven by key-participants), whereas challenges in relational integration (maintain confidence) and reconfiguration (refine activities) affected implementation negatively. Conclusion Although implementation did not sustain, network-broad PROM/PREM use in clinic and quality improvement matched professionals' motivation. This study provides recommendations to implement PROM/PREM meaningfully in practice in ways that support professionals in their drive towards patient-centered care. In order for PROM/PREM to fulfill their potential for value-based healthcare, our work highlights the need for sustainable IT infrastructures, as well as an iterative approach to refine their complex implementation into local contexts.